2002
DOI: 10.1194/jlr.m200108-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Physiological expression of macrophage apoE in the artery wall reduces atherosclerosis in severely hyperlipidemic mice

Abstract: We have previously reported that the introduction of macrophage apoE into mice lacking both apoE and the LDL receptor (apoE ؊ / ؊ /LDLR ؊ / ؊ ) through bone marrow transplantation (apoE ؉ / ؉ /LDLR ؊ / ؊ → apoE ؊ / ؊ /LDLR ؊ / ؊ ) produces progressive accumulation of apoE in plasma without affecting lipid levels. This model provides a tool to study the effects of physiologically regulated amounts of macrophage apoE on atherogenesis in hyperlipidemic animals. Ten-week-old male apoE ؊ / ؊ /LDLR ؊ / ؊ mice were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3
2

Relationship

5
4

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 31 publications
1
55
0
1
Order By: Relevance
“…A large body of published data suggest an atheroprotective role of apoE secreted by macrophages (14,15,(34)(35)(36)(37)(38). We have shown that reconstitution of apoE Ϫ/Ϫ mice with wild-type marrow results in a near-normalization of plasma cholesterol levels and a Ͼ50-fold reduction in atherosclerotic lesion area (35).…”
Section: Discussionmentioning
confidence: 89%
“…A large body of published data suggest an atheroprotective role of apoE secreted by macrophages (14,15,(34)(35)(36)(37)(38). We have shown that reconstitution of apoE Ϫ/Ϫ mice with wild-type marrow results in a near-normalization of plasma cholesterol levels and a Ͼ50-fold reduction in atherosclerotic lesion area (35).…”
Section: Discussionmentioning
confidence: 89%
“…We have previously reported that the absence of either macrophage apoE or ACAT1 increases atherosclerosis in LDLR Ϫ/Ϫ mice in the presence of a more severe hypercholesterolemia than that observed in the present study. 13,16 We interpret this finding to mean that the increased effect on atherogenesis resulting from absence of both macrophage ACAT1 and apoE in the apoE Ϫ/Ϫ model is most likely not mediated by the degree of plasma cholesterol changes.…”
Section: Discussionmentioning
confidence: 98%
“…Apolipoprotein (apo)E is a strong driver of cholesterol efflux, 14 and the increased atherogenicity of apoE-deficient macrophages may be due to defective elimination of cholesterol. 15,16 We and others have shown that macrophage apoE influences atherosclerosis both systemically, by controlling plasma cholesterol levels, and locally, by regulating cholesterol homeostasis in the macrophage. 15,17 Thus, in the present study, we used bone marrow transplantation (BMT) to generate apoE Ϫ/Ϫ mice with or without macrophage ACAT1 and apoE to address the effects of ACAT1 deletion on the development of atherosclerosis under both hypercholesterolemic and normocholesterolemic conditions, and we investigated the underlying molecular mechanisms of the accelerated atherosclerosis resulting from ACAT1 deficiency.…”
mentioning
confidence: 99%
“…25 Moreover, we have recently shown that a physiologically normal expression of macrophage apoE has antiatherogenic effects that are not limited to the foam cell lesion but extend into the more advanced stages of plaque growth. 26 Macrophage apoE expression is regulated by cellular cholesterol. 27 Two distal enhancers that specify apoE gene expression from macrophages contain conserved liver X receptor (LXR) response elements.…”
Section: Macrophage Foam Cell Formation and Cholesterol Homeostasismentioning
confidence: 99%